Novel sampling algorithm for DSP controlled 2 kW PFC converter. - Jinghai Zhou
This paper proposes a novel sampling algorithm for digital signal processing (DSP) controlled 2 kW power factor correction (PFCs) converters, which can improve switching noise immunity greatly in average-current-control power supplies. Based on the newly developed DSP chip TMS320F240. a 2 kW PFC stage is implemented. The novel sampling algorithm shows great advantages when the converter operates at a frequency above 30 kHz
Keywords: 2 kW; DSP control; PFC converter; TMS320F240 DSP chip; Average-current-control power supplies; Boost converter; Digital signal processing; Power factor correction; Sampling algorithm; Switching noise immunity